SPHINGOSINE-1-PHOSPHATE: A MISSING COFACTOR FOR THE E3 UBIQUITIN LIGASE TRAF2 - Alvarez, Sergio E. (2010)
TNF receptor-associated factor 2 (TRAF2) is a key component in NF-κB signaling triggered by TNF–α 1,2. Genetic evidence indicates that TRAF2 is necessary for polyubiquitination of receptor interacting protein 1 (RIP1) 3 that then serves as a platform for recruitment and stimulation of IκB kinase (IKK) leading to activation of the transcription factor NF-κB. Although TRAF2 is a RING domain ubiquitin ligase, direct evidence that TRAF2 catalyzes the ubiquitination of RIP1 is lacking. TRAF2 binds to sphingosine kinase 1 (SphK1) 4, one of the isoenzymes that generates the pro-survival lipid mediator sphingosine-1-phosphate (S1P) inside cells. Here we show that SphK1 and production of S1P is necessary for Lys 63-linked polyubiquitination of RIP1, phosphorylation of IKK and IκBα, and IκBα degradation, leading to NF-κB activation. Surprisingly, these responses were mediated by intracellular S1P independently of its cell surface G protein-coupled receptors. S1P specifically binds to TRAF2 at the N-terminal RING domain and stimulates its E3 ligase activity. S1P, but not dihydro-S1P, dramatically increased recombinant TRAF2-catalyzed Lys 63- but not Lys 48-linked polyubiquitination of RIP1 in vitro in the presence of the ubiquitin conjugating enzymes (E2) UbcH13 or UbcH5a. Our data reveal that TRAF2 is a novel intracellular target of S1P, and that S1P is the missing co-factor for TRAF2 E3 ubiquitin ligase activity, suggesting a new paradigm for regulation of Lys 63-linked polyubiquitination. These results also highlight the key role of SphK1 and its product S1P in TNF-α signaling and the canonical NF-κB activation pathway important in inflammatory, anti-apoptotic, and immune processes.